ANLIK BASINÇ YÜKÜ ETKİSİ ALTINDAKİ KONSOL BİR PLAĞIN DİNAMİK ANALİZİ - Haydar Uyanık; Zafer Kazancı (Havacılık ve Uzay Teknolojileri Dergisi, 2004)
The response of elastic structures to time-dependent pulses, such as sonic boom and blast loadings, constitutes a subject that is currently of much interest in the design of aeronautical and space vehicles. The air-blast load, which is the one type of extraordinary dynamic load, is produced as a consequence of explosion. In many applications ranging from aircrafts and submarines to pressure vessels, blast loadings and solving methods have a special importance. With the advent of structures and the effects of the blast loadings on their life-cycles, there is a need to reconsider the problem of dynamic behavior of plates under blast load.